N-(3-hydroxymethyl-β-carboline-1-yl-ethyl- 2-yl)-l-Phe: development toward a nanoscaled antitumor drug capable of treating complicated thrombosis and inflammation - Wu, Jianhui (Drug Des Devel Ther, 2017)
It is well documented that the surfaces of cancer cells, activated platelets and inflammatory cells are rich in P-selectin. N-(3-hydroxymethyl-β-carboline-1-yl-ethyl-2-yl)-l-Phe (HMCEF) is a P-selectin inhibitor capable of simultaneously inhibiting thrombosis and inflammation. Based on the knowledge that P-selectin is a common target for antithrombotic, anti-inflammatory and antitumor drugs, the aim of this study article was to estimate the possibility of HMCEF as a nanoscaled antitumor drug. Images of transmission electron micro scopy, scanning electron microscopy and atomic force microscopy proved that HMCEF forms nanoparticles with a diameter of <120 nm that promote delivery in blood circulation. In vitro HMCEF intercalates into calf thymus DNA, cuts off DNA pBR22 and inhibits the proliferation of cancer cells. In vivo HMCEF dose dependently (0.2, 2 and 200 nmol/kg per day) slows tumor growth in treated S180 mice, and has a minimal effective dose of 2 nmol/kg per day. At 200 nmol/kg per day, HMCEF does not affect the liver and the kidney of the treated S180 mice, and at 20,000 nmol/kg HMCEF does not affect the liver and the kidney of the treated healthy ICR mice. HMCEF is a promising antitumor drug, which is characterized by its high safety and efficacy in the prevention of the complications of thrombosis and inflammation in patients.